2012
DOI: 10.1021/pr2007957
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Eccrine Sweat: Implications for the Discovery of Schizophrenia Biomarker Proteins

Abstract: Liquid chromatography tandem mass spectrometry (LC-MS/MS) and multiple reaction monitoring mass spectrometry (MRM-MS) proteomics analyses were performed on eccrine sweat of healthy controls, and the results were compared with those from individuals diagnosed with schizophrenia (SZ). This is the first large scale study of the sweat proteome. First, we performed LC-MS/MS on pooled SZ samples and pooled control samples for global proteomics analysis. Results revealed a high abundance of diverse proteins and pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 17 publications
5
104
0
Order By: Relevance
“…In addition, we have shown that IL-6 does not appear in sweat in concentrations similar to, or even above that of plasma, counter to previous reports (Cizza et al 2008;Marques-Deak et al 2006). Therefore, in agreement with previous proteomic analysis of sweat (Raiszadeh et al 2012), it is unlikely that sweat acts as a plasma transudate, at least in the case of IL-6.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, we have shown that IL-6 does not appear in sweat in concentrations similar to, or even above that of plasma, counter to previous reports (Cizza et al 2008;Marques-Deak et al 2006). Therefore, in agreement with previous proteomic analysis of sweat (Raiszadeh et al 2012), it is unlikely that sweat acts as a plasma transudate, at least in the case of IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, sweat is known to contain a number of protease enzymes (Baechle et al 2006;Horie et al 1986) and protease inhibitors (Park et al 2011;Raiszadeh et al 2012). It is possible that during the 40 minute main collection period, these enzymes may be responsible for degrading IL-6, rendering it undetectable by ELISA.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…While several proteomic analyses of sweat have been reported (7,8), only five attempts at metabolomic analyses of sweat have been described. High-resolution nuclear magnetic resonance spectroscopy of sweat suggested the presence of several amino acids and lipid-associated groups (5,9).…”
Section: Sweat Collection and Transepidermal Water Loss Measurementmentioning
confidence: 99%
“…Using such methods total populations of peripheral blood mononuclear cells (PBMC), specific lymphocytes subpopulations as T-cells (both stimulated or unstimulated), or red blood cells (RBC) obtained from the blood stream of SCZ patients have already been studied. [41,85,86] One study using saliva [87] and another using sweat [88] have already been performed in the context of SCZ proteomics.…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%